[1, 2, 5]Oxadiazolo[3, 4-d]pyridazine 1, 5, 6-trioxides: efficient synthesis via the reaction of 3, 4-bis(hydroxyimino)methyl)-1, 2, 5-oxadiazole 2-oxides with a mixture of concentrated nitric and trifluoroacetic acids and structural characterization. Issue 32 (8th August 2018) - Ogurtsov, Vladimir A.; Dorovatovskii, Pavel V.; Zubavichus, Yan V.; Khrustalev, Victor N.; Fakhrutdinov, Artem N.; Zlotin, Sergei G.; Rakitin, Oleg A.
Graphical abstract: Highlights: An efficient synthesis of [1, 2, 5]oxadiazolo[3, 4- d ]pyridazine 1, 5, 6-trioxides. 4, 7-Dinitro[1, 2, 5]oxadiazolo[3, 4- d ]pyridazine 1, 5, 6-trioxide – high energy compound. Unusually long intracyclic NN bond of 1.668(5) Å in organic molecule. A mixture of concentrated nitric and trifluoroacetic acids as oxidizer. Abstract: An efficient synthesis of [1, 2, 5]oxadiazolo[3, 4- d ]pyridazine 1, 5, 6-trioxides (1 ) from 3, 4-bis(hydroxyimino)methyl)-1, 2, 5-oxadiazole 2-oxides using a mixture of concentrated nitric and trifluoroacetic acids has been developed. The scope of the unconventional reaction was established. The 4, 7-dinitro[1, 2, 5]oxadiazolo[3, 4- d ]pyridazine 1, 5, 6-trioxide 1f represents a new high energy compound, unfortunately with low thermal stability. The parent [1, 2, 5]oxadiazolo[3, 4- d ]pyridazine 1, 5, 6-trioxide 1c was studied by single-crystal X-ray diffraction analysis which revealed a planar molecule with an unusually long intracyclic NN bond of 1.668(5) Å and unexpected exo -cyclic bond angles at the nitroxyl nitrogen atoms. In the crystal, the molecules of 1c are bound to each other by strong π-π stacking and CH⋯O hydrogen bonding interactions into a three-dimensional framework that results in a high crystal density of 1.833 gcm −3 .